Alcohol and cannabinoid binges and daily exposure to nicotine in adolescent/young adult rats induce sex-dependent long-term appetitive instrumental learning impairment - Abela, Norbert; Haywood, Katie; Di Giovanni, Giuseppe (Frontiers in Behavioral Neuroscience, 2023)
Adolescence is a critical developmental period, concerning anatomical, neurochemical and behavioral changes. Moreover, adolescents are more sensitive to the long-term deleterious effects of drug abuse. Binge-like consumption of alcohol and marijuana, along with tobacco smoking, is a dangerous pattern often observed in adolescents during weekends. Nevertheless, the long-term effect of their adolescent co-exposure has not been yet experimentally investigated. Long-Evans adolescent male (n = 20) and female (n = 20) rats from postnatal day 30 (P30) until P60 were daily treated with nicotine (0.3 mg/kg, i.p.), and, on two consecutive ‘binging days’ per week (for a total of eight times), received an intragastric ethanol solution (3 g/kg) and an intraperitoneal (i.p.) dose of cannabinoid 1/2 receptor agonist WIN55,212-2 (1.2 mg/kg). These rats were tested after treatment discontinuation at > P90 for associative food-rewarded operant learning in the two-lever conditioning chambers for six consecutive days on a fixed ratio 1 (FR1) schedule followed by another six days of daily FR2 schedule testing, after 42 days rest. We found the main effects of sex x treatment interactions in FR1 but not in FR2 experiments. Treated females show attenuated operant responses for food pellets during all FR1 and the FR2 schedule, whilst the treated males show an impairment in FR2 but not in the FR1 schedule. Moreover, the treated females’ percentage of learners was significantly lower than female controls in FR1 while treated males were lower than controls in FR2. Our findings suggest that intermittent adolescent abuse of common drugs, such as alcohol and marijuana, and chronic tobacco exposure can cause significant long-term effects on motivation for natural reinforcers later in adulthood in both sexes. Females appear to be sensitive earlier to the deleterious effects of adolescent polydrug abuse, with both sexes having an increased likelihood of developing lifelong brain alterations.